From goddess to sukkubus: historical roots of demonization of a woman in Medieval culture - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to identifying the causes of the formation of anti-feminist position in medieval worldview. It discussed question about the existence of objective trend in development of culture (in particular, the religious consciousness), influenced this process. It is shown that the appearance of the negative attitudes towards women had deep historical and cultural reasons that go far beyond the Medieval culture, and its roots upward, paradoxically, to the phenomenon of sacralization women in archaic agrarian cultures.
Keywords: mythological consciousness; agrarian culture; the cult of fertility; matriarchy; chthonic mythology; sanctification of female power; the personification of the Great Mother; Moonʼs myths; mythology of snake; patriarchy; epic mythology; fighting against the snake; demonization of female personifications